The Four - Pools Mystery - Webster, Jean; Muneir, Shaimaa (Cairo Tadween Book 'n' Go, 2023)
In the four pools mystery the tyrannical plantation owner is deemed responsible for his own murder because of his mistreatment of the former slaves who continued in his employment after the war
Keywords: English Literature; English Stories